Menumbuhkan Semangat Belajar Remaja: Kajian Psikologi Pendidikan tentang Faktor Internal dan Eksternal Motivasi - Segara, Sukma Chalifah; Salma, Indah; Siregar, Pani Akhiruddin (EL-EMIR Institute, 2025)
This study aims to examine the internal and external factors that influence adolescents’ learning motivation from the perspective of educational psychology, as well as to formulate effective strategies for fostering their enthusiasm for learning. Adolescence is a crucial phase in shaping character and life direction, making learning motivation a vital aspect in supporting academic achievement and personal development. The method used in this study is library research, by collecting and analyzing various scholarly sources such as educational psychology textbooks, academic journals, and relevant previous studies. The findings show that internal factors such as learning interest, self-confidence, and life goals play a significant role in shaping adolescents’ motivation to learn. On the other hand, external factors such as parental support, teacher roles, school environment, and peer influence also have a strong impact. The lack of one or more of these factors can reduce motivation and engagement in the learning process. Therefore, synergy between family, school, and community environments is needed to create a supportive learning atmosphere. This study recommends a holistic and empathetic approach to nurturing adolescents’ learning motivation so they can grow into independent and high-achieving individuals.